2024
DOI: 10.3847/1538-4357/ad2456
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Plasma Waves and Downstream Magnetic Reconnection at a Reforming Quasi-parallel Shock

Quanming Lu,
Ao Guo,
Zhongwei Yang
et al.

Abstract: With the help of a two-dimensional particle-in-cell simulation model, we investigate the long-time evolution (near 100 Ω i 0 − 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Simulation and observation studies have suggested that the generation of LFWs is related to resonant interactions (Hellinger et al, 2007;Hull et al, 2020;Lu et al, 2024) or nonresonant interactions (H. Li et al, 2013;Wang et al, 2020). In our event, the obtained wave frequency f is ∼0.2 Hz, the wave phase velocity v ph is ∼300 km/s (mainly in the anti-sunward direction, -x in GSE), and the wave normal angle is ∼20°.…”
Section: Summary and Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Simulation and observation studies have suggested that the generation of LFWs is related to resonant interactions (Hellinger et al, 2007;Hull et al, 2020;Lu et al, 2024) or nonresonant interactions (H. Li et al, 2013;Wang et al, 2020). In our event, the obtained wave frequency f is ∼0.2 Hz, the wave phase velocity v ph is ∼300 km/s (mainly in the anti-sunward direction, -x in GSE), and the wave normal angle is ∼20°.…”
Section: Summary and Discussionmentioning
confidence: 54%
“…Low-frequency fast-magnetosonic waves (LFWs) usually have a wavelength larger than 1,000 km, comparable with the ion gyro-radii in the Earth's foreshock region (Hobrara et al, 2007;Wang et al, 2021). These waves are an important part of the macroscopic structure upstream of the bow shock and have been widely investigated over the last several decades (Gary et al, 1984;Hobrara et al, 2007;Lu et al, 2024;Tsurutani et al, 1983Tsurutani et al, , 2001Wang et al, 2020). They are right-hand polarized and typically have the frequencies less than ∼few Hertz, below the lower hybrid resonance frequency (Hobrara et al, 2007;Tsurutani et al, 1983Tsurutani et al, , 2001Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation